Clinical evaluation following the percutaneous transplantation of allogenic bone marrow-derived mesenchymal stem cells (aBM-MSC) in dogs affected by vertebral compression fracture. (December 2020) - Sharun, Khan; Rawat, Tushar; Kumar, Rohit; Chandra, Vikash; Saxena, Abhishek Chandra; Pawde, A.M.; Kinjavdekar, Prakash; Amarpal,; Sharma, G. Taru
Highlights: Intraspinal administration of allogenic bone marrow-derived mesenchymal stem cells (aBM-MSC) along with supportive therapy can be recommended as a therapeutic strategy for managing neural defects associated with non-deviating vertebral compression fractures in canine patients. Percutaneous technique described in this communication is a non-invasive and efficient method that can be used for transplanting stem cell into the target site without the need of any imaging or guidance system. Simplified implantation protocol that can be applied in the field level. Abstract: Stem cell therapy has been extensively evaluated for its potential in managing neuronal diseases and disorders. The present study was performed to evaluate the therapeutic potential of allogenic bone marrow-derived mesenchymal stem cells (aBM-MSC) for the management of neural defects associated with vertebral compression fracture (VCF) in canine. Six clinical cases presented with the history of neural defects secondary to non-deviating VCFs were included in the present study. All the animals were subjected to detailed clinical, radiological, and haematological investigations and observations were recorded. The neurological defects in each case were graded based on routine neurological examination. The aBM-MSCs were isolated, cultured, and characterized as per ISCT criteria from the bone marrow collected from healthy dogs presented for elective surgery. The prepared cell suspension containing aBM-MSC at 3rd passage was utilized for transplantation in the clinical cases of VCF. Following the intraspinal administration of aBM-MSC, the dogs were treated with methylcobalamin and gabapentin orally throughout the study period. Improvement was evaluated on the basis of a detailed neurological examination. Significant improvement in locomotor status and sensory functions was observed in all the cases. Findings of the present study suggest that intraspinal administration of aBM-MSCs along with supportive therapy can be recommended as a therapeutic strategy for managing neural defects associated with non-deviating VCFs in canine patients.